Long Noncoding RNA RUNXOR Promotes Myeloid-Derived Suppressor Cell Expansion and Functions via Enhancing Immunosuppressive Molecule Expressions during Latent HIV Infection - Zhang, Jinyu; Thakuri, Bal Krishna Chand; Zhao, Juan; Nguyen, Lam N; Nguyen, Lam N T; Khanal, Sushant; Cao, Dechao; Dang, Xindi; Schank, Madison; Lu, Zeyuan; Wu, Xiao Y; Morrison, Zheng D; et al. (The Journal of immunology (1950), 2021)
RUNX1 overlapping RNA (RUNXOR) is a long noncoding RNA and a key regulator of myeloid-derived suppressor cells (MDSCs) via targeting runt-related transcription factor 1 (RUNX1). We and others have previously reported MDSC expansion and inhibition of host immune responses during viral infections; however, the mechanisms regulating MDSC differentiation and suppressive functions, especially the role of RUNXOR-RUNX1 in the regulation of MDSCs in people living with HIV (PLHIV), remain unknown. In this study, we demonstrate that RUNXOR and RUNX1 expressions are upregulated in MDSCs that expand and accumulate in human PBMCs derived from PLHIV. We found that the upregulation of RUNXOR and RUNX1 is associated with the expressions of several key immunosuppressive molecules, including arginase 1, inducible NO synthase, STAT3, IL-6, and reactive oxygen species. RUNXOR and RUNX1 could positively regulate each other’s expression and control the expressions of these suppressive mediators. Specifically, silencing RUNXOR or RUNX1 expression in MDSCs from PLHIV attenuated MDSC expansion and immunosuppressive mediator expressions, whereas overexpressing RUNXOR in CD33+ myeloid precursors from healthy subjects promoted their differentiation into MDSCs and enhanced the expression of these mediators. Moreover, loss of RUNXOR-RUNX1 function in MDSCs improved IFN-γ production from cocultured autologous CD4 T cells derived from PLHIV. These results suggest that the RUNXOR-RUNX1 axis promotes the differentiation and suppressive functions of MDSCs via regulating multiple immunosuppressive signaling molecules and may represent a potential target for immunotherapy in conjunction with antiviral therapy in PLHIV.